Melacak Tafsir Nusantara: Tafsir Anom ( Tafsir Al-Qur’an Suci Bahasa Jawi Aksara Pegon) - Neny Muthi'atul Awwaliyah (UIN Siber Syekh Nurjati Cirebon, 2022)
This paper discusses one of the interpretations of the Qur'an written by Mohammad Adnan Tafsir using Javanese Arabic script Pegon. In this Tafsir it is unique that each letter, Mohammad Adnan, explains using Javanese language regarding the meaning of the title of the letter, the place where the letter was revealed, and mentions how many verses are in each letter. The method used in the interpretation is the Riwayah method. As for the style of interpretation in the Tafsir of the Holy Qur'an in Jawi, one of them is seen in the nuances of Fiqh. Tafsir al-Qur'an in Javanese, first printed in 1924 using Arabic Pegon